Public health impact of 2-, 4-, and 9-valent HPV vaccination in females on cervical and noncervical diseases in men and women under different coverage scenarios in China: A simulation study - Ibrahim Diakite; Jeffrey Kyle; Sujian Situ; Peng Bai; Xingxing Zhang; Wei Wang; Vincent Daniels (Taylor & Francis Group, 2023)
The high prevalence of human papillomavirus (HPV) infection in China suggests there would be a substantial positive health impact of widespread vaccination against HPV. We adapted a previously described dynamic transmission model of the natural history of HPV infection and related diseases to the Chinese setting to estimate the public health impact in China of 2-valent (with and without cross-protection), 4-valent, and 9-valent HPV vaccination strategies. The model predicted the incidence and mortality associated with HPV-related diseases, including cervical and noncervical cancers, genital warts, and recurrent respiratory papillomatosis (RRP), based on the various vaccination coverage rate (VCR) scenarios, over a 100-year time horizon. The public health impact of the 4 vaccination strategies was estimated in terms of cases and deaths averted compared to a scenario with no vaccination. Under the assumption of various primary and catch-up VCR scenarios, all 4 vaccination strategies reduced the incidence of cervical cancer in females and noncervical cancers in both sexes, and the 4-valent and 9-valent vaccines reduced the incidence of genital warts and RRP in both sexes. The 9-valent vaccination strategy was superior on all outcomes. The number of cervical cancer cases averted over 100 years ranged from ~ 1 million to ~ 5 million while the number of cervical cancer deaths averted was ~ 345,000 to ~ 1.9 million cases, depending on the VCR scenario. The VCR for primary vaccination was the major driver of cases averted.